Czy Moskwa powraca do zimnowojennej retoryki w komunikacji strategicznej? - Zadworny, Bartosz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In recent years, it is clear to see in Russia`s behaviour a return to the rhetoric that was so prominent during the Cold War. Particularly after the annexation of Crimea in 2014 and more broadly in the context of further tensions in relations with Ukraine. In this rhetoric, we are increasingly seeing terms such as "external threat", "information war" and "defensive sovereignty". Another aim of such behaviour is also to consolidate society, strengthen the sense of national identity and attempt to justify its domestic and foreign policies.
Keywords: komunikacja strategiczna; informacja; odstraszanie; NATO; strategic communication; information; deterrence